Ecologia alimentar de morcegos frugívoros em uma área de restinga do nordeste do Brasil e comportamento germinativo de espécies pioneiras após passagem pelo sistema digestório - Oliveira, Tamiris da Silva (2018)
The knowledge of the trophic interactions of fruit bats is fundamental to understand the role of these animals in the organization of tropical ecosystems. The present study, the fauna of fruit bats and food items that composed the diet of the species in the “Resting” of Northeast Brazil were determined. Similarity in the diet of the bats and the influence of seasonality and sex on the consumption of the resources were avaluated. Subsequently, the species of plants and seeds that passed through the digestive tract of the bats were identified for the evaluation of the germinative behavior (percentage, mean germination time, germination speed and synchronization index) of the seeds of four pioneer plant species (Cecropia pachystachya, Passiflora silvestris, Solanum asperum and Vismia guianensis). Seeds consumed by bats Artibeus lituratus and Carollia perspicillata were compared to unconsumed seeds (collected from fruits). Between October 2016 and September 2017, eight species of fruit bats were captured and nine species of plants identified in their fecal samples. The association between species based on diet content showed that these can be divided into three groups: specialists in Cecropia (A. lituratus and A. planirostris), specialist in Solanum (D. cinerea) and generalist (C. perspicillata). Carollia perspicillata contributed with seed samples throughout the year, having its diet influenced by seasonality. However, differences in the diet of males and females of this species were not observed. It was observed that the germination of C. pachystachya was significantly benefited after ingestion by A. lituratus. Seeds of S. asperum, P. silvestris and V. guianensis consumed by C. perspicillata presented neutral and negative effects on germinability in relation to seeds collected from fruits. The results of the present study indicated that the species seem to adapt to the different conditions of food supply during the dry and rainy periods, modifying their diet or moving to other areas where they can consume fruits of their preference. In addition, the same species of bat can produce distinct effects on the germinative behavior of seeds consumed, as well as different bats can contribute in a differentiated way in the establishment rates of plants in the restinga, mainly in the initial stages of succession.